Cloning and characterization of the MboII restriction-modification system. - Bocklage, H (Nucleic Acids Res, 1991)
The two genes encoding the class IIS restriction-modification system MboII from Moraxella bovis were cloned separately in two compatible plasmids and expressed in E. coli RR1 delta M15. The nucleotide sequences of the MboII endonuclease (R.MboII) and methylase (M.MboII) genes were determined and the putative start codon of R.MboII was confirmed by amino acid sequence analysis. The mboIIR gene specifies a protein of 416 amino acids (MW: 48,617) while the mboIIM gene codes for a putative 260-residue polypeptide (MW: 30,077). Both genes are aligned in the same orientation. The coding region of the methylase gene ends 11 bp upstream of the start codon of the restrictase gene. Comparing the amino acid sequence of M.MboII with sequences of other N6-adenine methyltransferases reveals a significant homology to M.RsrI, M.HinfI and M.DpnA. Furthermore, M.MboII shows homology to the N4-cytosine methyltransferase BamHI. IMAGES: